2012
DOI: 10.1002/ajh.23337
|View full text |Cite
|
Sign up to set email alerts
|

Fludarabine, cytarabine, and attenuated‐dose idarubicin (m‐FLAI) combination therapy for elderly acute myeloid leukemia patients

Abstract: We performed a phase II trial to evaluate the efficacy and safety of the modified fludarabine, cytarabine, and attenuated-dose idarubicin (m-FLAI) regimen in elderly acute myeloid leukemia (AML) patients. Elderly (60 years) AML patients who had not previously received chemotherapy were enrolled in the study. Patients received two consecutive cycles of m-FLAI chemotherapy as an induction. The m-FLAI regimen comprised fludarabine (25 mg/m 2 , days 1-4), cytarabine (1,000 mg/m 2 , days 1-4), and attenuated-dose i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 42 publications
1
14
1
3
Order By: Relevance
“…Overall, 67% of patients achieved a CR, 17% of patients were refractory, and the mortality was 16%. Although higher CR rates have been observed in some studies, these have generally excluded patients with significant comorbidities or poor performance status . The mortality rate of 20.5% in our older cohort is somewhat higher than those reported in recent studies, for example, Lowenberg et al .…”
Section: Discussioncontrasting
confidence: 66%
“…Overall, 67% of patients achieved a CR, 17% of patients were refractory, and the mortality was 16%. Although higher CR rates have been observed in some studies, these have generally excluded patients with significant comorbidities or poor performance status . The mortality rate of 20.5% in our older cohort is somewhat higher than those reported in recent studies, for example, Lowenberg et al .…”
Section: Discussioncontrasting
confidence: 66%
“…The CR, CRp, and CRi were 39.3%, 9.1%, and 6.1%, respectively. These response rates are quite promising when comparing with 56.5% CR rate in modified fludarabine, cytarabine, and attenuated‐dose idarubicin (m‐FLAI) regimen in newly diagnosed elderly patients with AML . Also our response is also comparable or better than many investigational therapies although all clinical settings of each trial were not directly comparable .…”
Section: Discussionmentioning
confidence: 79%
“…Also, BM BLAST <5% at R E had a marginal significance. This implies that eradicating residual leukemia cells which are found at early evaluation after C‐FLAG could increase the possibility of CR as shown in m‐FLAI study that second induction therapy gave additional CR . Therefore, additional attenuated early reinduction therapy if there are residual leukemic cells at early evaluation could be possible option for improving CR rate.…”
Section: Discussionmentioning
confidence: 96%
“…High-quality evidence showed that the risk of death was 1.17 times higher when patients 5 years younger were compared with patients 5 years older than the median age (hazard ratio [HR] [95% confidence interval per 5-year increase in age], 1.17 [1.11-1.23]). 29,56,[60][61][62][63][64][65][66][67][68][69][70][71][72] High-quality evidence showed that the risk of death was 1.72 times higher when patients with worse performance status (ECOG score of 21) were compared with those with better performance status (ECOG score of ,2) (HR [95% confidence interval], 1.72 [1.47-2.01]). 60,64,[73][74][75][76][77][78][79][80][81][82][83]123 There was also high-quality evidence showing that the risk of death was 1.59 times higher when patients with more comorbidities (HCT-CI score of 31) were compared with those with fewer comorbidities (HCT-CI score of ,3) (HR [95% confidence interval], 1.59 [1.28-1.98]).…”
Section: Prognosis In Older Adults With Amlmentioning
confidence: 99%